Effects on nitrogen-acetone ice induced by energetic heavy ion collisions. (July 2015) - Alcantara, K F; de Barros, A L F; da Silveira, E F; Rothard, H; Boduch, P
Synopsis: The radiolysis of a mixture of acetone and nitrogen condensed at 13 K by 40-MeV 58 Ni 11+ ions was studied. The bombardment with heavy ions is highly efficient for inducing chemical reactions in ices. The dissociation rate of acetone mixed with nitrogen as a function of the fluence is determined from a sequence of infrared spectra. The formation of new molecular species due to the irradiation is investigated and their cross-sections are calculated